Enhanced Vigenere encryption technique for color images acting at the pixel level - Chemlal, Abdelhakim; Tabti, Hassan; El Bourakkadi, Hamid; Rrghout, Hicham; Jarjar, Abdellatif; Benazzi, Abdelhamid (Institute of Advanced Engineering and Science, 2024)
The pixel unit is an essential component of many encryption schemes. In the beginning two substitution tables, separately constructed from chaotic maps namely, the logistic map, slanted tent map, and the AJ map, which has a very high Lyapunov exponent and is very sensitive to start factors, are used to make modifications at the pixel level. These S-Boxes have a maximum period and are produced from several linear congruential generators. This approach uses newly developed confusion and diffusion functions connected to the recently built substitution tables to perform a refined Vigenere strategy. The purpose of this chaining is to defend the system from differential assaults. Extensive simulations on a variety of image formats and sizes confirm our process’s robustness against identified dangers.